2004
DOI: 10.1103/physrevb.69.155411
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostructural and electronic properties of hydrogenated silicon nanoclusters in the ground and excited state

Abstract: Electronic and structural properties of small hydrogenated silicon nanoclusters as a function of dimension are calculated from ab initio technique. The effects induced by the creation of an electron-hole pair are discussed in detail, showing the strong interplay between the structural and optical properties of the system. The distortion induced on the structure after an electronic excitation of the cluster is analyzed together with the role of the symmetry constraint during the relaxation. We point out how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 43 publications
(45 reference statements)
9
79
0
Order By: Relevance
“…This fact has been previously discussed for the case of fully hydrogenated Si-nc, where, by total energy calculations 14,15,16 , it has been demonstrated that the usual trend is recovered also for the emission for Si-nc with diameter ≥ 1 nm. Having the absorption and emission gaps, we can now give an estimate of the Stokes shift fully including excitonic effects (the BS-LF results).…”
supporting
confidence: 59%
“…This fact has been previously discussed for the case of fully hydrogenated Si-nc, where, by total energy calculations 14,15,16 , it has been demonstrated that the usual trend is recovered also for the emission for Si-nc with diameter ≥ 1 nm. Having the absorption and emission gaps, we can now give an estimate of the Stokes shift fully including excitonic effects (the BS-LF results).…”
supporting
confidence: 59%
“…The average Si-Si bond length is found to be contracted compared to the bulk; the contraction is reduced and tends towards the bulk value as the size of the nanocrystal is increased. Looking at individual Si-Si bonds, it is found that the outer shell is contracted, which has been interpreted as due to surface stress, 63,64 61 In classical linear elasticity, inhomogeneities, whether in vacuo or embedded in a material, have size-independent elastic fields. 65 This is the result of neglecting surface energies which can be justified when the ratio of surface to volume atoms is small.…”
Section: Calibrationmentioning
confidence: 99%
“…This can be done by exploiting the virial theorem in MD simulations, 36 but not in geometry optimization calculations. For these, a promising approach is to exploit the experimental 43 and computational 61 result that bonds in the bulk-like core of sufficiently large alkane-terminated diamond phase Si nanocrystals display elastic properties similar to the bulk for a range of sizes. P eff can then be estimated for a range of systems and pressures from the compression of core bonds after quasistatic geometry optimization.…”
Section: Calibrationmentioning
confidence: 99%
“…Photoluminescence measurements have shown that these predictions are qualitatively correct, but with a varying exciton binding energy of 0.01 to 0.9 eV in phosphorene, this technique will underestimate the band gap of black phosphorus by a similar amount, which depends on the static dielectric constant of the surrounding medium. [56][57][58] In addition, surface defects, contamination, and oxidation of samples may introduce further experimental uncertainty. In fact, results so far are quite varied: in one study, a trilayer photoluminesced at 1.60 eV, while, in another, the measured value was 0.97 eV (see optical gaps, Table 1).…”
Section: Optical Absorption In 2d Phosphorus: Backgroundmentioning
confidence: 99%